Formulating a Research Problem Statement - Yusuf, Saldy (Faculty of Nursing, Universitas Hasanuddin, 2024)
Academic writing is a means of reporting research findings to the public, allowing them to be known, replicated, or applied. However, academic writing differs significantly from non-academic writing. It is inherently objective, grounded in research facts, and supported by citations from existing studies to substantiate or refute arguments. In contrast, non-academic writing is subjective and does not require the use of factual evidence in every analysis. This fundamental difference poses a challenge for academic writing, particularly for novice researchers.